Erratum: “Conditions for one-photon coherent phase control in isolated and open quantum systems” (2010)
Coherent control of observables using the phase properties of weak light that induces one-photon transitions is considered. Measurable properties are shown to be categorizable as either class A, where control is not possible, or class B, where control is possible. Using formal arguments, we show that phase control in open systems can be environmentally assisted.